Emotion work and gender inequality in transnational family life - Chávez, Sergio; Paige, Robin; Edelblute, Heather (Journal of Family Issues, 2021)
This study examines the emotion work of non-migrant women as they seek to sustain family life across borders. We draw on in-depth interviews with 59 non-migrant women in Guanajuato, Mexico who had immigrant spouses in the USA to assess emotion work dynamics between partners. Our analysis reveals that non-migrant women do emotion work that entails imagining lives abroad and then tailoring emotional support that addresses the needs of spouses. We also discuss how the difficulties associated with prolonged separation leads women to suppress their own needs and feelings, which can lead to emotional burnout and marital conflict. Putting non-migrant women and their activities at the center of our analysis highlights the emotional costs of migration for those who remain behind and the ways in which emotion work is a highly gendered activity that reinforces inequality through communication. We highlight how women’s subordinated status in transnational Mexican families and the need to keep the remittances flowing help explain why emotion work falls largely on women. © The Author(s) 2021.
Keywords: 2000 à aujourd'hui; amériques; discipline; famille; le coût émotionnel de la migration; mexique; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; sociologie; thématiques; travail; travail émotionnel